Pengaruh Pembiayaan Murabahah, Istishna, Dan Ijarah Terhadap Kinerja Keuangan Bank Umum Syariah - Salsabila Husna; Murniati (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to determine the effect of murabahah, istishna and ijarah financing on the financial performance of Sharia Commercial Banks listed on the Indonesia Stock Exchange. There are 13 Sharia Commercial Banks in Indonesia in the 2020-2022 period. This research data was obtained from statistical data or annual financial reports for the 2020-2022 period which can be seen on the official website www.ojk.go.id. This research is descriptive research using a purposive sampling method, the sample used was 4 Sharia Commercial Banks which were included in the criteria and the research hypothesis used was multiple linear analysis. The results of this research show that murabahah financing and Istishna has a significant positive effect on the financial performance of Sharia Commercial Banks, ijarah financing has a negative effect on the financial performance of Sharia Commercial Banks listed on the Indonesia Stock Exchange for the 2020-2022 period.